2012
DOI: 10.1371/journal.pone.0047928
|View full text |Cite
|
Sign up to set email alerts
|

Outcome following Nerve Repair of High Isolated Clean Sharp Injuries of the Ulnar Nerve

Abstract: ObjectiveThe detailed outcome of surgical repair of high isolated clean sharp (HICS) ulnar nerve lesions has become relevant in view of the recent development of distal nerve transfer. Our goal was to determine the outcome of HICS ulnar nerve repair in order to create a basis for the optimal management of these lesions.MethodsHigh ulnar nerve lesions are defined as localized in the area ranging from the proximal forearm to the axilla just distal to the branching of the medial cord of the brachial plexus. A met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 76 publications
0
25
0
Order By: Relevance
“…This is in part due to the large number of axons required to power the hand intrinsics as well as the distance required for axons to regenerate before reaching their motor endplate targets. As such, ulnar nerve injuries proximal to the elbow have an especially poor prognosis 55 61. To improve the results after such injuries, the anterior interosseous nerve (AIN) branch to the pronator quadratus (PQ) has been used to selectively innervate the motor branch of the ulnar nerve 41 53 54 56.…”
Section: Introductionmentioning
confidence: 99%
“…This is in part due to the large number of axons required to power the hand intrinsics as well as the distance required for axons to regenerate before reaching their motor endplate targets. As such, ulnar nerve injuries proximal to the elbow have an especially poor prognosis 55 61. To improve the results after such injuries, the anterior interosseous nerve (AIN) branch to the pronator quadratus (PQ) has been used to selectively innervate the motor branch of the ulnar nerve 41 53 54 56.…”
Section: Introductionmentioning
confidence: 99%
“…Tinel believed that late worsening of clawing is related to loss of tonus of the paralyzed interosseous muscles . Recently, Post et al revised the literature on outcomes of the repair of sharp lesions of the ulnar nerve around and above the elbow. Surgeons had assumed that traumatic isolated ulnar nerve injuries had resulted in loss of flexion of the distal phalanx of the ring and little fingers.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical repair of ulnar nerve lesions do relatively poor as compared, for instance, to the radial and median nerves. 17 In 1991, Birch and Raji had conducted a detailed and comprehensive study on 108 median and ulnar nerve injuries that were managed by either primary, delayed repair, or grafting. They concluded that primary repair is the best with achieving a few excellent results particularly in young age patients.…”
Section: Discussionmentioning
confidence: 99%